Transient Hepatitis B Antigenemia After Vaccination in Pediatric Patient - Solin, Ro Shinta Christina; Bahasoan, Yusuf (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
The hepatitis B surface antigen (HBsAg) test is a perioperative examination used for hepatitis B screening to prevent and control bloodborne infections. The interpretation of HBsAg results in post-vaccination cases requiring vigilance. A 2-month-old pediatric patient was referred to the hospital for colostomy surgery. The patient undergoes routine screening for surgery, including screening for hepatitis B. The laboratory test obtained reactive HBsAg results using the Chemiluminescent Microparticle Immunoassay (CMIA) method. The HBsAg confirmatory testing was done, and reactive results were obtained. Patients are vaccinated against hepatitis B at 0 and 2 months. On the seventeenth day after the initial assessment, a second examination was conducted, and the results were negative for HBsAg, anti-HBs, total anti-HBc, and anti-HBe. Hepatitis B surface antigenemia may occur after vaccination in pediatric patients. Increasing patient and hospital staff awareness of this phenomenon aids in the reduction of unnecessary medication or therapy.